Design of Temporary Storage for Hazardous Waste at Politeknik Perkapalan Negeri Surabaya - Setiani, Vivin; Sholihah, Mar'atus; Kurniasih, Dewi; Widiarti, Yuning; Budiyanto, Ekky Nur; Khumaidi, Agus; Wibowo, Sekarsari; Setyawati, Emeralda Eka Putri; Astutik, Rina Puji (Universitas Diponegoro, 2025)
Politeknik Perkapalan Negeri Surabaya has workshops or laboratories that generate hazardous waste from practical learning activities. Currently, hazardous waste is not stored in accordance with regulations, it will pose a danger to the environment and human health. Therefore, this research requires a design for hazardous waste storage that complies with the Minister of Environment and Forestry Regulation number 6 of 2021. The design of fire extinguisher requirements is based on the Regulation of the Minister of Manpower and Transmigration of the Republic of Indonesia No. Per.04/Men/1980 and the design of lighting based on SNI 03-6575-2001. This research discusses the design of hazardous waste storage, including the characteristics of hazardous waste, the design of packaging and the supporting facilities. The characteristics of hazardous waste at the Politeknik Perkapalan Negeri Surabaya consist of flammable waste, toxic waste, and infectious waste. While, the packaging for hazardous waste is equipped with symbols and labels according to their characteristics and volume. The design of the hazardous waste storage building at the Politeknik Perkapalan Negeri Surabaya has dimensions of 11 m x 7 m, equipped with 12 lights and light fire extinguishers, taking into account the location, facilities, and emergency response.